Analisis Kimia Minuman Fungsional Daun Kersen Dan Biji Buah Pepaya Dengan Penambahan Gula Aren - Aldita Idrak; Muh Tahir; Siti Aisa Liputo (Jambura Journal of Food Technology, 2022)
Functional drinks are drinks that contain elements of nutrients and can provide good benefits for the health of the body. This functional drink is made from cherry leaves, papaya seeds and palm sugar. Some of the components that play a role in all ingredients are the content of flavonoids, triterpene tannins, alkaloids, saponins, and phenols which function as pharmacolyses for the body. The purpose of this research is to produce functional drinks that are innovative and suitable for consumption as well as to maximize the benefits of cherry leaves, papaya fruit seeds and palm sugar in beverage processing, especially papaya fruit seeds which are often wasted. The data obtained from each test were collected and analyzed using the 1-factor Completely Randomized Design (CRD) method which was arranged with four treatments and three replications. The treatments used consisted of three formulations (palm sugar, papaya fruit seeds, cherry leaves) namely B0(0:50:200), B1(50:50:150), B2 (100:50:100) B3 (150:150). 50:50). Each treatment was repeated three times. Observation parameters consist of antioxidant activity, total dissolved solids, sweetness and organoleptic levels with the highest antioxidant yield of 51.220 ppm, total dissolved solids 10.330Brix, and sweetness level of 11,000Brix.